Evaluation of coal ore to reduce the sulphur content and improve its quality - Quijandría Lavarello, Juan Carlos (2016)
Develop essential aspects relating to mineral coal; its main physico-chemical characteristics, petrográficas, mineralogical, processes of washability and float. The coal studied comes from mines San Alejandro, Oyón, is a bituminous coal of high content volatile, with good energy performance and low concentration of ash and sulfur. We have studied the removal of mineral matter with emphasis on the Sulfur Coal Fixed improvement and calorific value of coal mines of San Alejandro, Oyón. Principio del formulario. The study of characterization of the mineral coal has identified a granulometry average of 93.51% to a mesh -200, a hardness 3, apparent density of 1.30 g/cm3, real density of 1.72 g/cm3 and a porosity of 0.79%. With regard to the immediate analysis the averages of the samples on dry matter basis are of 0.78 % moisture, 18.73 % of volatile matter, 17.33 % ash and 60.24 % of fixed carbon, Gross Calorific Value OF 7257.31 Kcal/kg and a lower calorific value of 7239.80 Kcal/kg. The microscopic analysis shows the presence of 96.91 % of Graphite (grf) and 3.09% Pyrite (py). He fractions of fine of these coals have been treated by Washability and float with foaming agents. The results obtained by washability we have a decrease of ash content average of 5.14%, an elimination average of 2.18% of sulfur, a slight increase of Volatile Matter to $18.65 % and Coal fixed at 62,43 %. The results of float is has a remarkable decline of Ashes of 55.35% and 36.61 Sulfur per cent; an increase of fixed carbon 16.91% and the calorific value increased from 7257.31kcal/kg to 8141.22 Kcal/Kg.